Underkill Scalable Capabilities for Military Operations amid Populations - Gompert, David C. (RAND Corporation, 2009)
The U.S. military is ill-equipped to strike at extremists who hide in populations. Using deadly force against them can harm and alienate the very people whose cooperation U.S. forces are trying to earn. To solve this problem, a new RAND study proposes a "continuum of force"--a suite of capabilities that includes sound, light, lasers, cell phones, and video cameras. These technologies are available but have received insufficient attention.